Cardiac phosphocreatine deficiency induced by GPA during postnatal development in rat - Pelouch, V; Kolár, F; Khuchua, Z A; Elizarova, G V; Milerová, M; Ost'ádal, B; Saks, V A (Molecular and cellular biochemistry, 1996)
The effect of chronic administration of beta-guanidinopropionic acid (GPA) on the protein profiling, energy metabolism and right ventricular (RV) function was studied in the rat heart during the weaning and adolescence period. GPA was given in tap water (1-1.5%) using pair drink controls. The feeding of animals with GPA solution for a six week period resulted in elevation of heart to body weight ratio due to body growth retardation. GPA accumulated in the myocardium up to 67.37 +/- 5.3 mumoles.g dry weight and the tissue content of total creatine, phosphocreatine and ATP was significantly decreased to 15%, 9% and 65% of control values respectively. Total activity of creatine kinase (CK) was not changed, but the proportion of mitochondrial (Mi) CK isoenzyme was decreased; the percentage of MB isoenzyme of CK was significantly higher. GPA treatment resulted in an elevation of the content of cardiac collagenous proteins and decrease of non-collagenous proteins in the heart; in parallel, a decrease of the collagen I to collagen III ratio was detected. The function of the RV was assessed using an isolated perfused heart with RV performing pressure-volume work. As compared to pair-drink controls, RV function was significantly impaired the GPA group: at any given right atrial filling pressure, the RV systolic pressure and the rate of pressure development were decreased by almost a factor of two. Elevation of the RV diastolic pressure with increasing pulmonary artery diastolic pressure was also significantly steeper in the GPA group which also showed decrease of cardiac output, especially at high outflow resistance. It may be assumed that chronic administration of GPA deeply influenced metabolic parameters, protein profiles and contractile function of the developing heart. On the other hand, concentrations of glucose, total lipids and triglycerides in blood plasma were not affected. All these data confirm the concept that the CK system is of central importance both for heart function and for the regulation of normal growth of cardiac myocytes.
Keywords: Coronary Circulation; Sarcoplasmic Reticulum; Rats; krevní tlak; kreatinkinasa; Carbon Monoxide; Rats, Wistar; mužské pohlaví; oxid uhelnatý; krysa rodu Rattus; sarkoplazmatické retikulum; guanidiny; Isoenzymes; Phosphocreatine; myokard; zvířata; Blood Pressure; Myocardium; izoenzymy; Heart; propionáty; potkani Wistar; Guanidines; Creatine Kinase; fosfokreatin; koronární cirkulace; srdce; Propionates; Male; Animals